Stabilizing a class of time delay systems using the Hermite-Biehler theorem - Oliveira, V. A.; Teixeira, MCM; Cossi, L. (Elsevier B.V., 2003)
In this paper we use the Hermite-Biehler theorem to establish results for the design of fixed order controllers for a class of time delay systems. We extend results of the polynomial case to quasipolynomials using the property of interlacing in high frequencies of the class of time delay systems considered. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: stability; delay systems; closed-loop control; interlacing; quasipolynomials